Labial osteolipoma, clinical and surgical management of an infrequent disease - Panico, Ignacio; Gilligan, Gerardo Marcelo; Gelmanw, Liliana; Panic, René Luis (Journal of Oral Diagnosis, 2019)
Lipomas are relatively infrequent benign neoplasms of connective tissue that can involve oral mucosa. Different histological subtypes of oral lipomas were previously described in current literature. The aim of this work is to report a clinical case of an 83-year-old male, who presented with a 20-years-old labial mass. Surgical removal was performed, and the histopathological diagnosis reported an oral Osteolipoma (OL). Discussion: There are previous reports of oral lipomas that have histologically presented a combination with other cell lines such as bone and cartilaginous tissue within the tumor. The rarity of its presentation makes this entity an infrequent diagnosis for clinicians and specialists in Oral Medicine. The provisional diagnosis could be aided with X-ray when the mass exam revealed indurated areas and calcifications. There are few cases described of OL in this oral subsite. Because of its unusual presentation, OL of the oral mucosa is a true challenge in oral diagnosis.